Incidence and mortality rate of esophageal cancer has decreased during past 40 years in Hebei Province, China - He, Yutong; Wu, Yan; Song, Guohui; Li, Yongwei; Liang, Di; Jin, Jing; Wen, Denggui; Shan, Baoen (Chinese Journal of Cancer Research, 2015)
Background: Hebei province is located in North of China with of approximately 6% of whole national population. It is known as a high-risk area for esophageal cancer in China and worldwide. The aim of our study was to estimate the esophageal cancer burden and trend in Hebei Province. Methods: Eight cancer registries in Hebei Province submitted cancer registry data to the Hebei Provincial Cancer Registry Center. All data were qualified and compiled for cancer statistics in 2011. The pooled data were stratified by gender and age group (0, 1-4, 5-9, 10-14…80+). Incidence and mortality rates were age-standardized to World Segi’s population standard and expressed per 100,000 persons. In addition, proportions and cumulative incidence/mortality rates for esophageal cancer were calculated. Esophageal cancer mortality data during the periods 1973-1975, 1990-1992, and 2004-2005 were extracted from the national death surveys. Mortality and incidence rate data from Cixian and Shexian were obtained from population-based cancer registries in each county. Results: The estimated number of newly diagnosed esophageal cancer cases and deaths in 2011 in Hebei Province was 24,318 and 18,226, respectively. The crude incidence rate of esophageal cancer was 33.37/100,000 (males, 42.18/100,000 and females, 24.31/100,000). The age-standardized rate by world standard population (ASRW) was 28.09/100,000, ranking third among all cancers. The esophageal cancer mortality rate was 25.01/100,000 (males, 31.40/100,000 and females, 18.45/100,000), ranking third in deaths among all cancers. The mortality rates of esophageal cancer displayed a significant decreasing trend in Hebei Province from 1973-1975 (ASRW =48.69/100,000) to 2004-2005 (ASRW =28.02/100,000), with a decreased rate of 42.45%. In Cixian, the incidence of esophageal cancer decreased from 250.76/100,000 to 106.74/100,000 in males and from 153.86/100,000 to 75.41/100,000 in females, with annual percentage changes (APC) of 2.13 and 2.16, while the mortality rates declined with an APC of 2.46 for males and 3.10 for females from 1988 to 2011. In Shexian, the incidence rate decreased from 116.90/100,000 to 74.12/100,000 in males and from 46.98/100,000 to 40.64/100,000 in females, while the mortality rates declined, with an APC of 4.89 in males from 2003 to 2011. Conclusions: Although the incidence and mortality rates of esophageal cancer remain high, an obvious decreasing trend has been observed in Hebei Province, as well as in high-risk regions, such as Cixian and Shexian, over the past 40 years.